CONSUMER SOVEREIGNTY AT A TIME OF GLOBALIZATION AND ICT EXPANSION - Bogdan Mróz (Polityki Europejskie, Finanse i Marketing)
Living in a globalized world with robustly expanding information and communications technology, the 21st century consumer is exposed to innovative business models emerging in the cyberspace. On the one hand, this offers a chance of consumer empowerment and wider choice but on the other, previously unknown issues and threats are making themselves felt, among them electronic surveillance and loss of privacy. In the present article, an attempt is made to diagnose the chances for, and threats to, consumer sovereignty resulting from globalization and swift development of new information and communications technology.